THE INFLUENCE OF THE WASHINGTON CONSENSUS PROGRAMME ON THE TRANSITIONAL ECONOMIES OF EASTERN EUROPE – A FIRM-LEVEL ANALYSIS - Howard-Jones, Peter; Hölscher, Jens (Economic Annals, 2020)
This research explores the effectiveness of the Washington Consen-sus (WC) programme as a mechanism for improving national welfare in transition and emerging economies, using its inter-nalisation by the European Union (EU) as a proxy. The results indicate that there is a positive benefit to firms with accession to the EU, leading to greater productivity improvement and performance advantages than in non-member states. Foreign direct investment directly benefitted those firms that became investees, with little evidence of spillovers to domestic companies. The vertical nature of the investment, with an emphasis on international production net-works that utilise significant levels of for-eign inputs, infers protection of intellectual property and a reduction in value added, with results indicating a failure to achieve an export multiplier. There is evidence of substantial benefits accruing to firms in receipt of loans, but the apparent paucity of their availability may imply market fail-ure. The gains made by innovative firms do not appear to do justice to the initiatives undertaken and may indicate a dilution of national innovative capacity.